A new species of the genus Xya Latreille, 1809 from China (Orthoptra, Tridctyloidea, Tridactylidae) - Cao, Cheng-Quan; Shi, Jian-Ping; Yin, Zhan (Zootaxa, 2018)
A new species of the genus Xya Latreille, 1809 from Sichuan, China is described in this paper. The new species Xya sichuanensis sp. nov. is similar to Xya japonica (Haan, 1844), but differs from latter by head with yellow stripe on both sides, vertex with two yellow stripes on the inner margin of eyes, pronotum with yellow stripe on both sides, tegmina with two small yellow spots, fore and mid legs black, with yellow spots and hind wing yellow. Type specimens are deposited in the College of Life Science, Leshan Normal University, Leshan 614004, China.